A Promising Mandibular Molar Trait in Ancient Populations of Ireland - Jaimin D. Weets (Dental Anthropology, 2009)
A novel morphologic feature on the human dental enamel of the permanent mandibular molars is described. The character, named MMPT (mandibular molar pit-tubercle), is situated mesial and occlusal to the position often occupied by the protostylid on the buccal aspect of cusp 1. Three grades of variation, a pit, a groove, and a tubercle were observed, described and categorized for study. The study groups consisted mainly of archaeological specimens from Ireland, representing approximately 5,000 years of prehistoric and early historic populations on the island, dating from the Neolithic (ca. 4,000-1,800 B.C.) through the Early Christian era (ca. A.D. 400-1170). All lower molars (representing 432 individuals) were studied, ranging from 129 to 179 scorable molars depending on tooth type. The third molar more commonly expressed all forms of MMPT than the first or second molars, with approximately 30% of all third molars exhibiting a form of MMPT (28% of lower left third molars and 33% of lower right third molars). The most commonly expressed form of MMPT was Grade 1, the pit form, most commonly on third molars. Individual Viking specimens from Ireland also exhibited MMPT, and the trait appears to be present in East Asian modern humans at a markedly lower rate of expression, and in Homo pekinensis. Further research will clarify any relationships between MMPT, paramolar tubercles, paramolar structures and the protostylid, as well as the utility of MMPT in dental anthropological biodistancing studies.